Pengaruh Ethical Leadership dan Organizational Justice terhadap Intention to Leave yang dimediasi oleh Kepuasan Kerja pada Karyawan Perusahaan Retail di Depok. - Nabilla Baina; Lucy Warsindah (STIE AMKOP, 2023)
This study aims to analyze the influence of Ethical Leadership and Organizational Justice on Intention to Leave mediated by Job Satisfaction. This research is a descriptive quantitative research that used the hypothesis testing method. The analysis methods used are univariate and multivariate with the help of SPSS 25 and AMOS 22 software. The number of respondents used in this study was 153 retail employees taken by census. The results of the hypothesis test in the study show that there is a negative influence between Ethical Leadership on Intention to Leave, there is a positive influence between Ethical Leadership on Job Satisfaction, there is a negative influence between Organizational Justice on Intention to Leave, there is a positive influence between Organizational Justice on Job Satisfaction, there is a negative influence between Job Satisfaction on Intention to Leave, Job Satisfaction can mediate the influence of Ethical Leadership on Intention to Leave and Job Satisfaction can mediate the influence of Organizational Justice on Intention to leave.